PENGARUH PRICE FAIRNESS DAN BRAND IMAGE TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK MINAT BELI ULANG (Survei pada Konsumen Rown Division Kota Surakarta) - Siti Mukaromah; Marjam Desma Rahadhini; Rahayu Triastity (Universitas Slamet Riyadi, 2020)
Aim of the research are to explain 1) influence of price fairness to customer satisfaction; 2) influence of brand image to customer satisfaction; 3) influence price fairness to repurchase intention; 4) influence brand image to repurchase intention; 5) influence customer satisfaction to repurchase intention. This research at Rown Division Surakarta. Sample measurement is used as 115 respondents with nonprobability sampling technique and purposive sampling method. Data analysis technique used is Structural Equation Medeling analysis technique. Research result indicates that there is influence of direct price fairness towards customer satisfaction with a value of CR = 2,638 and value of p = 0,008; influence of direct brand image towards customer satisfaction with a value of CR = 2,891 and value of p = 0,003; influence of indirect price fairness towards repurchase intention with value of CR = 0,394 and value of p = 0,694; influence of direct brand image towards repurchase intention with value of CR = 2,389 and value of p = 0,017; and influence of direct customer satisfaction towards repurchase intention with value of CR = 2,280 and value of p = 0,023. Based on aim of research, suggestion for the Rown Division Surakarta is to pay attention to customer satisfaction of factors and brand image, so that cutomer feel satisfied and always want to make a repurchase intention.